The Complexity of the BRICS in Eurasia - Mohammad Ali Samay (Köz-gazdaság, 2021)
Russia, China and India (RIC) are the three most significant powers in the Eurasian region. Their influence on and role in security, political and economic organizations in Eurasia is outstanding. In bilateral perspective, Russia and India, respectively Russia and China represent major country relationships in the region. In multilateral perspective, beside numerous regional and international organizations the three countries are also the key members of the BRICS group. This paper focuses on both the positive and the negative impact of BRICS institutions, policies, action plans, and practical projects on Eurasian security, political and economic cooperation.